High-resolution NMR-based metabolic detection of microgram biopsies using a 1 mm HRμMAS probe. Issue 24 (13th November 2015) - Nishiyama, Yusuke; Endo, Yuki; Nemoto, Takahiro; Bouzier-Sore, Anne-Karine; Wong, Alan
Abstract : A 1 mm HRμMAS prototype probe is introduced for 1 H NMR-based metabolic detection of heterogeneous biospecimens. Abstract : A prototype 1 mm High-Resolution micro-Magic Angle Spinning (HRμMAS) probe is described. High quality 1 H NMR spectra were obtained from 490 μg of heterogeneous biospecimens, offering a rich-metabolite profiling. The results demonstrate the potential of HRμMAS as a new NMR analytical tool in metabolomics.